1996
DOI: 10.1038/bjc.1996.105
|View full text |Cite
|
Sign up to set email alerts
|

Tumour cells surviving in vivo cisplatin chemotherapy display elevated c-myc expression

Abstract: Summary The c-myc oncogene has been extensively implicated in cell proliferation, cell differentiation and programmed cell death. Aberrant expression of the c-myc gene product has been observed in a range of tumours and has also been implicated in cisplatin (cis-dichlorodiammineplatinum)-mediated chemoresistance. A solid transplantable tumour model in syngeneic DA rats was subjected to treatment with cisplatin to determine the impact of such therapy on endogenous c-myc gene expression. Serially

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
0
29
1
Order By: Relevance
“…20,21 However, to our knowledge the high levels of c-myc expression in AML demonstrated in our study have not been reported previously. One reason that this area has not been intensively studied might be that translocations involving c-myc and overexpression of c-myc by extrachromosomal copies (double minute) in AML are rare.…”
Section: Figurecontrasting
confidence: 50%
“…20,21 However, to our knowledge the high levels of c-myc expression in AML demonstrated in our study have not been reported previously. One reason that this area has not been intensively studied might be that translocations involving c-myc and overexpression of c-myc by extrachromosomal copies (double minute) in AML are rare.…”
Section: Figurecontrasting
confidence: 50%
“…New predictive factors are needed, because conventional histopathologic factors do not accurately predict the likelihood that an individual patient will respond to cytotoxic chemotherapy. This is a possible area for future investigation, as some studies have implicated expression of c-myc in resistance to cisplatin-based chemotherapy in multiple tumour types (Walker et al, 1996), in MDR1 expression in rhabdomyosarcoma cell lines (Prados et al, 1996), and in resistance to 5-fluorouracil and cisplatin in squamous cell carcinomas of the head and neck (Riva-Lavielle, 1994). A rigorous study, designed specifically to address the relationship between c-myc amplification and drug and hormone resistance in breast cancer, may provide valuable insight into more effective treatment strategies.…”
Section: Amplification Of C-myc: Role As An Independent Prognostic Famentioning
confidence: 99%
“…Furthermore, c‐MYC has been found to be involved in drug resistance. Tumour cells resistant to cisplatin chemotherapy in vivo display elevated c‐myc expression , and c‐myc antisense oligonucleotides sensitize human colorectal cancer cells to chemotherapeutic drugs . Recent study has been shown that c‐MYC overexpression decreased the expression level of the bridging integrator 1, leading to increased poly (ADP‐ribose) polymerase 1 (PARP1) activity and resistance to cisplatin .…”
Section: Introductionmentioning
confidence: 99%